Special Issue of Pathogenesis of Pregnancy-Related Complications, 2023 - Hromadnikova, Ilona (International journal of molecular sciences, 2024)
This Special Issue mainly focuses on preeclampsia (PE), haemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome, gestational diabetes mellitus (GDM), foetal growth restriction (FGR), small-for-gestational-age foetuses (SGA), miscarriage, stillbirth, first-episode psychosis (FEP) during pregnancy, and pregnancy-related acute kidney injury (PR-AKI) [...].
Keywords: komplikace těhotenství; Female; Fetal Growth Retardation; Diabetes, Gestational; narození mrtvého plodu; Pregnancy; ženské pohlaví; Humans; lidé; Pregnancy Complications; Stillbirth; růstová retardace plodu; preeklampsie; těhotenství; gestační diabetes; Pre-Eclampsia